Bass Fish Measurement System (Bass) - Nadzirah Irfani, Fathi (Universiti Malaysia Sarawak (UNIMAS), 2023)
The measurement of fish length is an essential factor in aquaculture sector since it is used for a variety of purposes, including monitoring, and determining fish development, gender, age, and reproduction. Till now, businesses that specialise in fish farming utilise measuring boards made of wood or acrylic plastic. However, this conventional technique puts the fish through a great deal of strain when measuring their length while they are still alive. In addition, utilising a measuring board to manually measure the length of each fish, one at a time, is a time-consuming process. This process will acquire high cost, manual labour and expert knowledge for the measurement process. Hence, this project presents an intrusive method for measuring the length and weight of Asian sea bass (Lates Calcarifer) using image processing and statistical analysis for measurement data study. This Bass Fish Measurement System was developed to measure the fish length and weight while estimating its age accurately. The BASS was designed by using an image processing tool which consists of data acquisition, image pre-processing, and measurement in Python with OpenCV library. The dataset image used in BASS was collected from Stesen Perikanan Darat Samariang Batu. The image acquisition and image pre-processing consist of pre-treatment, segmentation, and feature extraction stages. Further analysis was carried out to compare the estimated measurement with the exact measurement. The lateral view was chosen as it more accurate in term of total percentage error, Mean Absolute Error and Root Mean Square Deviation for length, weight, and age respectively in the three cases. Therefore, this BASS project will have an efficient and accurate data result for future analysis or research on fish measurements.